Effects of early weaning on feedlot performance of bulls and steers - Schlickau, E.K.; Marston, T.T.; Brethour, J.; Dikeman, Michael E.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred Hereford × Angus calves (n = 103) were used to determine the effects of early weaning on feedlot performance of bulls and steers. Treatments were: 1) early-weaned (117 days of age) bulls, 2) early-weaned steers, 3) normal-weaned (220 days of age) bulls, and 4) normal-weaned steers. Early-weaned calves were placed on a grower ration at an average age of 134 days and on a finishing ration at 182 days of age. Normal-weaned calves were placed on a finishing ration at 242 days of age. Weight, feed intake, and ultrasound measurements were recorded during the feeding period. Three early-weaned cattle were removed due to chronic bloat, and four early-weaned cattle died in the feedlot. The feedlot period was terminated at either 358 or 387 days of age. Early-weaned cattle had greater average daily gains early in the feedlot period, but normal-weaned cattle had greater gains later in the feedlot period. Excluding the initial weight at 117 days of age, early-weaned cattle maintained heavier weights throughout the feeding period. Bulls had greater average daily gains until feedlot entry of normal-weaned calves, but steers had greater average daily gains later in the feedlot period, resulting in similar final weights. For early-maturing British-type cattle, early weaning resulted in heavier final weights, but it may not be the most viable management strategy because of disadvantages in animal health. Overall, there was no growth-performance advantage for leaving males intact, suggesting that the implant regimen used for these steers was sufficient to compensate for the expected loss in performance when bulls are castrated.
Keywords: Beef; Early weaning; Feedlot performance; Bulls; Steers